Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1001/jamaoto.2016.2029
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Dyspnea Outcomes After Endoscopic Airway Surgery for Laryngotracheal Stenosis

Abstract: IMPORTANCE Endoscopic airway surgery is a frequently used procedure in the management of laryngotracheal stenosis (LTS); however, no established outcome measures are available to assess treatment response. OBJECTIVE To assess acoustics and aerodynamic measures and voice- and dyspnea-related quality of life (QOL) in adult patients with LTS who undergo endoscopic airway surgery. DESIGN, SETTING, AND PARTICIPANTS This case series compared preoperative measures and postoperative outcomes among adult patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 35 publications
(108 reference statements)
2
10
0
Order By: Relevance
“…Idiopathic subglottic stenosis is well suited to assessment with PROMs because the primary clinical manifestation of this disease is a perceptual and psychosocial symptom with an impact on many facets of QOL . Several groups have used PROMs to show that patients with airway stenosis tend to improve along many dimensions after surgery to widen the glottis and/or subglottic airway, including along the dimensions of voice and dyspnea symptoms . Our model agrees with the inclusion of both of these dimensions, as well as including questions about cough (which can be persistent in ISGS) and general overall health.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Idiopathic subglottic stenosis is well suited to assessment with PROMs because the primary clinical manifestation of this disease is a perceptual and psychosocial symptom with an impact on many facets of QOL . Several groups have used PROMs to show that patients with airway stenosis tend to improve along many dimensions after surgery to widen the glottis and/or subglottic airway, including along the dimensions of voice and dyspnea symptoms . Our model agrees with the inclusion of both of these dimensions, as well as including questions about cough (which can be persistent in ISGS) and general overall health.…”
Section: Discussionsupporting
confidence: 67%
“…16 Several groups have used PROMs to show that patients with airway stenosis tend to improve along many dimensions after surgery to widen the glottis and/or subglottic airway, including along the dimensions of voice and dyspnea symptoms. 9,[22][23][24] Our model agrees with the inclusion of both of these dimensions, as well as including questions about cough (which can be persistent in ISGS) and general overall health.…”
Section: Discussionsupporting
confidence: 64%
“…The critical finding of the present study was that most patients with LTS reported significant postoperative improvement in dyspnea, and a DI decrease of 4 was identified as the MCID using anchor‐based methodology. The use of this statistical method, along with the higher number of patients in this cohort, may improve accuracy over previously reported MCID value . This finding is important because it provides a method to define treatment efficacy of clinical significance using a readily available PRO questionnaire.…”
Section: Discussionmentioning
confidence: 78%
“…Thus, this makes it a versatile tool that can be employed in various clinical scenarios and is easy to administer. As a recently developed PRO instrument, the DI is utilized in few published studies, and only one study by Samad et al defined the MCID of the DI as a value of 5.4 using distribution methods in this patient population . De Guzman et al identified the MCID of the DI as a decrease of 8 in adolescents with exercised‐induced PVFM .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation